Levels of Qur’anic text reception in Arabic culture From fascination to attempts at interpretation - Mahazem, Aziz (Journal of Human Sciences, 2021)
The Holy Quran was first revealed to the Prophet, peace be upon him, and then went down in extended times and different places with which the recipients of the Quranic text expanded, and their psychological and practical responses varied from what they heard. We are faced with a phenomenon of revelation that extends to distant times of uninterrupted contact of the Divine with humans. The text has emerged as a new and unfamiliar discourse in Arab culture, but with the most eloquent phrase. Knowing the position of the Arabs on it is of great importance not only in understanding the text, but even in knowing how to build it itself, because the Qur’an as we know came to change a reality that has settled time, and appeared as a vital communication with its recipients argue them, and respond about the doubt that they raised against it, and their judgments